Penanganan Pengaduan dan Pengawasan Penaatan Lingkungan Hidup PT. X Kabupaten Mojokerto oleh Dinas Lingkungan Hidup Provinsi Jawa Timur - Aliya Shabira Kusriyandini; Khuliyah Candraning Diyanah; Aditya Sukma Pawitra (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Industry industry plays an important role in economic development, but it also has negative impacts on the environment, such as air, water and soil pollution. negative impacts on the environment, such as air, water and soil pollution. One of one industrial sector that has the potential to cause pollution is the activated carbon industry, which in its production process produces solid, liquid and activated carbon industry, which in the production process produces solid, liquid, and gas. This study aims to determine the mechanism of handling complaints and supervision of environmental compliance by the East Java Provincial Environmental Agency (DLH) against PT. X, which is an activated carbon industry. (DLH) of East Java Province against PT X, an activated carbon industry in Mojokerto Regency, which is suspected of causing industry in Mojokerto Regency that is suspected of polluting the environment. The method used used is descriptive qualitative with data collection techniques through observation and in-depth interviews. The results showed that community complaints complaints related to dust pollution from the company's production activities have been followed up through verification and field inspection by the DLH. followed up through verification and field inspection by the DLH of East Java Province. East Java Province. Field findings indicate violations of environmental environmental regulations, especially in controlling air emissions. Research This research emphasizes the importance of assertive and continuous supervision from DLH in order to encourage industries to be more compliant with regulations in order to protect the quality of the environment and the health of surrounding communities. environment and the health of the surrounding community.